Association between Coping Strategies and Infertility Stress among a Group of Women with Fertility Problem in Shiraz, Iran - A Aflakseir; M Zarei (JRI, 2013)
Background: Studies have shown that individuals with fertility problems experience psychosocial problems. The use of various coping strategies seems to have different impacts on women with infertility stress. The aim of this study was to examine the role of coping strategies (active-avoidance, passive-avoidance, active-confronting and meaning based) in predicting infertility stress among a group of women seeking infertility treatment in Shiraz. Methods: One hundred twenty infertile women were recruited from several infertility clinics in Shiraz using convenience sampling method. The participants completed research measures including the Infertility Problem Stress Inventory and the Ways of Coping Scale (passive-avoidance, active-avoidance, active-confronting, meaning-based). Multiple regression analysis was used for data analysis. A p-value less than 0.05 was considered as statistically significant. Results: The findings showed that participants had the highest scores on passive-avoidance coping strategies followed by meaning-based coping, active-confronting coping and active-avoidance coping. The findings also indicated that women who utilized more active-avoidance coping strategies reported less infertility stress. Furthermore, the results of regression analysis demonstrated that two coping strategies including active-avoidance (β=0.35, p<0.001) and meaning-based coping (β=-0.50, p<0.001) predicted infertility stress significantly. Moreover, meaning-based coping strategy was the strongest predictor of low infertility stress. Conclusions: The present study showed that the majority of infertile women used passive-avoidance coping strategy. Furthermore, those who perceived their infertility problem as meaningful had a low infertility stress, while those who used active-avoidance coping strategies had high infertility stress.
Keywords: Coping skills, Female, Fertility, Infertility, Psychological, Stress